Neuronal oscillations and functional connectivity of paced nostril breathing: A high-density EEG study. - Anita B Frohlich; Flavio Frohlich; Miriam Sklerov (PLoS ONE)
Controlling nostril airflow through hand manipulations is an ancient yoga technique that has been suggested to provide targeted modulation of neuronal excitability and regulation of autonomic function, which is known to be lateralized in the brain. Here, we examined if unilateral and alternate nostril breathing differentially impacts brain network oscillations measured by high-density EEG in healthy control participants with no prior experience in breathing techniques. We found that paced nostril breathing both decreased alpha/mu oscillations over central and parietal areas and increased frontal midline and occipital theta oscillations when comparing to spontaneous breathing. Alternate nostril breathing suppressed alpha/mu oscillation more than left nostril breathing. Unilateral nostril breathing resulted in an ipsilateral increase in alpha connectivity while left nostril breathing increased anterior-posterior midline theta connectivity. In contrast to the EEG results, heart rate, heart rate variability, and cognitive performance assessed with a working memory task did not differ significantly by breathing condition. Our results add to the existent literature on nasal breathing by demonstrating changes in cortical oscillations and connectivity during a task that combined slow breathing with manual nasal pathway modulation.